Gender analysis of cross-border migration in rural border communities of Ipokia local government area, Ogun State, Nigeria - Kehinde Olayinka Popoola; Gbenga John Oladehinde; Afolabi Francis Fatusin (Economic and Environmental Studies (E&ES), 2017)
The study examined gender dimension of cross border migration in rural border communities of Ipokia local government area, Ogun State, Nigeria. The study specifically examined socio-economic characteristics of migrants, pattern of migration between male and female migrants and reasons for cross border migration in the study area. Multistage sampling technique was used in selecting 184 migrants (both male and female of equal size) in the study area. The study revealed that the mean age of male migrants was 41 years while that of female migrants was 36.3 years. Also, larger percentage of male (75%) and female (51.1%) migrants earn above Nigeria minimum wages (18,000). This was an indication that cross border migration has positive effect on migrants' standard of living. Major reasons for cross border migration (push factor) for male migrants included poor income, bad economic condition, poverty and few employment opportunities and unfavourable climatic condition, while poor income and poverty were major reasons adduced by female migrants. Moreover, good access to land, commerce and better income reasons were the major considerations for choosing destination area by male migrants while good access to land, marriage, to join family members and better income were the considerations for choosing destination area by female migrants in Nigeria (pull factors). The study concluded that despite the increase in cross border migration into the study area, patterns and reasons for cross border migration vary between men and women.
Keywords: 330; Gender; Cross border migration; Rural border communities; Ogun; Nigeria